Screening of biological actives extracts from Annona squamosa - C., Babu; Devi, P. Rama; Kombiah, P. (International Journal of Biological Research, 2014)
The aim of the present study is to focus on the cytotoxicity and antimicrobial activities from Annona squamosa plant seed extracts. The plant A. squamosa seed was extracted with various solvents like chloroform, methanol, hexane, petroleum ether and acetone. The antimicrobial activities of all these extracts were determined by disc diffusion method against Pseudomonas aeruginosa, Proteius vulgaries, Staphylococcus aureus and Escherichia coli pathogens. Methanol, hexane and acetone extracts of A. squamosa showed highest anti-microbial activity against all pathogens. Cytotoxic activity of A. squamosa seed extract was tested using Artemia salina (Brine shrimp) bioassay. In cytotoxicity study, extract caused 86% mortality of  Brine shrimp larvae after 24 h at a concentration of 500 µg/mL.   Keywords: Antimicrobial Activity, Cytotoxicity Activity. Extract, Pathogens, Solvent.